Detection of cancerous kidney tissue by means of SERS spectroscopy of extracellular fluid. (29th August 2017) - Velicka, M.; Pucetaite, M.; Urboniene, V.; Ceponkus, J.; Jankevicius, F.; Sablinskas, V.
Abstract: We present a novel approach for detection of cancerous kidney tissue areas by measuring surface enhanced Raman scattering (SERS) spectra of extracellular fluid taken from kidney tissue. The method is based on spectral analysis of the cancerous and normal tissue areas in order to find the specific spectral markers. The samples were prepared by sliding the kidney tissue over a substrate—calcium fluoride optical window. For producing the SERS signal, the dried extracellular fluid film was covered by silver nanoparticle colloidal solution. In order to suppress fluorescence background, the measurements of the dried samples were performed in the NIR spectral region with the Raman excitation wavelength of 1, 064 nm. The most significant spectral differences—spectral markers—were found in the wavenumber region between 400 and 1, 800 cm −1, where spectral bands related to various vibrations of carbohydrates, amino acids, and nucleic acids are located. Spectral markers in the SERS spectra are different from those in IR absorption spectra. The SERS spectroscopic method has a potential to be used directly during the surgery. Abstract : We present a novel approach for the detection of cancerous kidney tissue areas by measuring the surface enhanced Raman scattering (SERS) spectra of extracellular fluid taken from the kidney tissue. The method is based on spectral analysis of the cancerous and normal tissue areas in order to find the specific spectral markers.